Comparison of preconvective environments between warm-sector and frontal heavy rainfall events in South China - Wan, Yijing; Wang, Dongyang; Wang, Donghai (Frontiers in Earth Science, 2025)
This study aims to identify the environmental differences between frontal heavy rainfall (FHR) and warm-sector heavy rainfall (WSHR), which frequently occur during early summer (April-June) over South China. Using 14 years of hourly rain-gauge data and high-resolution radiosonde observations, a total of 132 WSHR events and 84 FHR events are quantitatively investigated. FHR events occur most frequently in late May, while WSHR events demonstrate an increasing trend from April to June. WSHR events exhibit a pronounced diurnal variation, with a peak at 0800 LST (Local Standard Time, LST = UTC +8 h). In contrast, FHR events have a peak at 0400 LST. The WSHR and FHR events typically occur under favorable convective conditions characterized by abundant water vapor, moderate convective available potential energy (CAPE), and moderate to severe deep wind shear. Compared to FHR events, WSHR events are associated with more abundant water vapor at 500 hPa, greater warm cloud depth, a lower lifting condensation level, and stronger warm advection. FHR events are characterized by more water vapor in the lower troposphere, stronger instability, and stronger 0–6 km wind shear. Additionally, WSHR events exhibit higher wind speed below 800 hPa than FHR events, while the wind speed in the upper troposphere for FHR events is 3–4 m s-1 larger than that in WSHR events. The thermodynamic characteristics associated with WSHR and FHR events, as revealed in this study, have significant implications for enhancing our understanding of heavy rainfall in South China.